Legal stains in the Malaysian Islamic Banking practices of AlIjarah Thumma Al Bai' (AITAB) - Hassan, Rusni; Yusoff, Adnan; Muneeza, Aishath (World Business Institute, 2012)
IjarahThumma al Bai’ (AITAB) is a modern product of Islamic banking which was incepted more than ten years ago. It shows the novel constituent of Islamic banking. AITAB is the alternative for conventional hire-purchase. The popularity of this product have boosted among the customers, but there are certain legal stains in this product which needs to be highlighted and rectified in order to engrave Islamicity in the product. The main objective of this paper is to analyze the legal issues involved in AITAB and to give appropriate recommendations to curb these predicaments.